Peranan Pergerakan Air Dalam-Tanah dalam Menurunkan Aliran Permukaan - Enni Dwi Wahjunie; Dwi Putro Tejo Baskoro; Suria Darma Tarigan (Jurnal Ilmu Pertanian Indonesia, 2021)
The main cause of flooding and erosion that creates critical land in various regions in Indonesia is surface runoff. The surface runoff will occur if rainfall exceeds the capacity of soil water absorption (infiltration capacity). The soil management of each land use could improve the infiltration capacity. The water movement both on the surface and in the soil determines the water infiltration. This study predicts surface runoff based on the infiltration rate of various land uses and rainfall in the Ciliwung Watershed. A series of studies were performed in the upstream and middle areas of the watershed. Observations of soil properties, water movement, and rainfall were carried out in various dry land uses. The results showed that the soil's physical properties mostly determine the constant infiltration rate, which affected the water movement in the soil. The initial water content, the degree of saturation of the initial moisture content, and the soil's physical properties determine the time of constant infiltration rate. The value of constant rate infiltration and the time of its achievement determine the amount of surface runoff that occurs. Keywords: hydraulic conductivity, run off, soil management, time achievement of infiltration capacity